Application of numerical method to analyse the trend of babies with abnormalities - Emmanuel, Sabastine; Saratha Sathasivam,; Hazleen Marleesa A. H. Hafeez,; Nurizzati Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Compartmental models are commonly used in epidemiology to study the dynamics of infectious diseases, but they can also be used to model other health outcomes, such as the incidence of babies born with abnormalities. In this study, we present a two-compartment model that divides the population of new-borns into babies born with abnormalities (unhealthy) and babies born without abnormalities (healthy). The model assumes that the incidence of abnormalities is a function of certain factors, such as maternal age or environmental factors, and that babies can transition between the compartments depending on their health status. We present the mathematical equations for this model and demonstrate how it can be simulated using MATLAB code. Our results show how the model can be used to simulate the dynamics of babies born with abnormalities over time, providing insights into the factors that influence their incidence and the effectiveness of interventions to reduce their occurrence. This model can be adapted and extended to explore more complex scenarios and study the impact of different interventions on the health outcomes of new-borns.